Eve : how the female body drove 200 million years of human evolution - Bohannon, Cat (Alfred A. Knopf, 2023)
"In Eve, Cat Bohannon answers questions scientists should have been addressing for decades. With boundless curiosity and sharp wit, Bohannon covers the past 200 million years to explain the specific science behind the development of the female sex. Eve is not just a sweeping revision of human history, it's an urgent and necessary corrective for a world that has focused primarily on the male body for far too long. Bohannon's findings, including everything from the way C-sections in the industrialized world are rejiggering women's pelvic shape to the surprising similarities between pus and breast milk, will completely change what you think you know about evolution . . . and women. A 21st-century update of Our Bodies, Ourselves, Eve offers a paradigm shift in our thinking about what the female body is and why it matters"--